Cultural expression in the Old Kingdom Elite Tomb - Verma, Sasha (Archaeopress Egyptology, 2014)
'Cultural Expression in the Old Kingdom Elite Tomb' considers the material and immaterial culture left behind by the ancient Egyptian elite in their tombs starting some 5000 years ago. The book intends to understand this culture reflecting the 'intention' of the ancient Egyptians. All these 'intentions' are now inaccessible to us, a paradox indeed. The author starts by examining the ways in which other Egyptologists have understood tomb culture over the past century